2022
DOI: 10.7759/cureus.25620
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Spectrum of Hodgkin's and Non-Hodgkin's Lymphoma: A Tertiary Care Cancer Hospital Study in Pakistan

Abstract: IntroductionLymphomas are a heterogeneous group of disorders that arise primarily from lymphoid tissue and are categorized based on histological features and immunophenotypes. The distribution and frequency of different types of lymphoma vary in different parts of the world. This study aimed to document the frequency and clinicopathological characteristics of various types of lymphoma in our population to understand the ever-increasing burden of disease and formulate the optimal management and prevention plans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…There were 369 males and 179 females in our study, with a male-to-female ratio of 2.06:1. The male-to-female ratio was reported by Aslam et al [15] in patients with NHL is close to ours: 1.83:1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There were 369 males and 179 females in our study, with a male-to-female ratio of 2.06:1. The male-to-female ratio was reported by Aslam et al [15] in patients with NHL is close to ours: 1.83:1.…”
Section: Discussionsupporting
confidence: 92%
“…Jayanta et al found that the GIT is the most common extranodal site for NHL involvement, based on a retrospective analysis of pictorial positron emission tomography (PET) scans from different regions [18]. Our study showed similar results to those reported in other studies [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…4 In Pakistan, the annual incidence of non-Hodgkins chronic lymphomas is reported to be up to 8.4 per 100,000 and majority are B-cell lymphomas (BCLs). [5][6][7] They manifest clinically with a variety of symptoms depending on their histological subtype, aggressive versus indolent, and the site of involvement, exhibiting significant patient-topatient variation. Patients may present with localised or generalised lymphadenopathy, hepatosplenomegaly, cytopenias or constitutional symptoms.…”
Section: Introductionmentioning
confidence: 99%